The G-protein alpha-subunit gene CGA1 is involved in regulation of resistance to heat and osmotic stress in Chlamydomonas reinhardtii - Lee, C. S.; Ahn, W.; Choi, Y. E. (Cellular and Molecular Biology, 2017)
In eukaryotic cells, many important functions of specific G-proteins have been identified, but microalgal G-proteins are poorly studied. In this work, we characterized a gene (CGA1) encoding the G-protein Î±-subunit in Chlamydomonas reinhardtii. Independent knockdown mutants of CGA1 were generated via RNA interference (RNAi). CGA1 expression levels were consistently and significantly reduced in both independent CGA1 mutant cell lines (cga1). Both cga1 mutants had a higher survival rate at 35°C in comparison with the wild type. This stronger resistance of the cga1 mutants became more evident during simultaneous exposure to heat and osmotic stress. The stronger resistance of the CGA1 knockdown mutants to the two stressors was accompanied with significant morphological alterations”both cell size and cell wall thickness were different from those of the wild type. This finding supports the roles of CGA1 in C. reinhardtii morphology in response to stressors. To further understand biochemical mechanisms of the CGA1-mediated resistance, we thoroughly analyzed the level of reactive oxygen species (ROS) and the expression of several heat shock proteins or MAP kinase genes as possible downstream effectors of CGA1. Our data clearly indicated that CGA1 is implicated in the regulation of resistance to heat or osmotic stress in C. reinhardtii via HSP70A and MAPK6. Because the G-protein Î±-subunit is highly conserved across microalgal species, our results should facilitate future biotechnological applications of microalgae under extreme environmental conditions.